Ammonia Synthesis: Ruthenium Catalysts Promoted by Lanthanide Oxyhydrides with High Hydride‐Ion Mobility for Low‐Temperature Ammonia Synthesis (Adv. Energy Mater. 4/2021). Issue 4 (27th January 2021) - Ooya, Kayato; Li, Jiang; Fukui, Keiga; Iimura, Soshi; Nakao, Takuya; Ogasawara, Kiya; Sasase, Masato; Abe, Hitoshi; Niwa, Yasuhiro; Kitano, Masaaki; Hosono, Hideo
Abstract : In article number 2003723 Masaaki Kitano, Hideo Hosono and co‐workers show that lanthanide oxyhydrides such as LaH3−2 x O x and CeH3−2 x O x, with a high hydride‐ion conductivity effectively promote the activity of a Ru catalyst for low‐temperature ammmonia synthesis. The surface or local mobility of hydride ions rather than bulk hydride ion conductivity play a crucial role in the high catalytic performance.